Pemanfaatan Model Pembelajaran E-Learning dalam Pembelajaran Sosiologi Selama Masa Pandemi Covid-19 - Herdin Muhtarom (SAP (Susunan Artikel Pendidikan), 2021)
With the Covid-19 pandemic outbreak, all activities can only be done at home or in popular terms in the world of education, namely School Form Home (SFH). In learning activities, it can only be done through the use of information and communication technology media that can be accessed at home. The purpose of this study is to determine the use of the E-learning learning model in sociology learning at SMAN 2 Pandeglang in 2021 during the Covid-19 pandemic. By using the Mixed Methods research methodology with the media research instrument questionnaire distributed to students majoring in social studies at SMAN 2 Pandeglang. The results showed that the E-learning model applied in the sociology subject at SMAN 2 Pandeglang was very effective in the learning model during the Covid-19 pandemic with 27 respondents (62.8%) agreeing to implement the E-learning model in sociology material at SMAN 2 Pandeglang.